Visible-Light-Induced Hydrogen-Atom-Transfer Catalysis for the Regioselective Hydroacylation of N-Sulfonylimine Esters with Aldehydes - Chi, Zhiyong; Huang, Siyuan; Tang, Guo; Zhao, Qianyi; Gong, Lei (Synlett, 2025)
The hydroacylation of unsaturated π-systems with aldehydes offers a direct and atom-economical route for introducing both a hydrogen atom and an acyl group into an organic molecule. Whereas hydroacylation reactions with alkanes and alkenes are well established, transformations involving imines have been much less successful. Existing approaches often favor C–C bond formation over C–N bond formation, due to the inherent properties of imines and acyl radicals. We present a photochemical approach that specifically targets N-sulfonylimine esters in combination with aldehydes. This reaction is facilitated by a decatungstate-salt-mediated double hydrogen-atom-transfer (HAT) activation that uniquely promotes the formation of C–N bonds under mild and simple conditions. Our method permits the efficient synthesis of a broad spectrum of distinctive N-sulfonyl N-carbonyl amide products with exclusive regioselectivity. We expect this streamlined method to expand the synthetic toolkit available for constructing complex nitrogen-containing compounds.
Keywords: visible light; photocatalysis; hydrogen atom transfer; hydroacylation; imines; regioselectivity